Numerical Simulation of Flow around Rigid Rotor in Forward Flight - Abalakin, I. V.; Bobkov, V. G.; Kozubskaya, T. K.; Vershkov, V. A.; Kritsky, B. S.; Mirgazov, R. M. (Fluid dynamics, 2020)
The study is devoted to the numerical simulation of flow around the rigid helicopter main rotor in forward flight based on the averaged Navier—Stokes equations in a noninertial reference frame. The calculations are performed using the in-house code NOISEtte, whose distinctive feature is the use of schemes with edge-based reconstruction of variables on unstructured mixed-element mesh, together with the commercial ANSYS CFX software package. The numerically obtained aerodynamic characteristics of the main rotor are compared with the data of physical experiment.